Lipoid proteinosis (Urbach-Wiethe syndrome). Issue 10 (October 1979) - Feiler-Ofry, V; Lewy, A; Regenbogen, L; Hanau, D; Katznelson, M B; Godel, V
Abstract : A Jewish-Iranian family suffered from lipoid proteinosis. The 8 affected siblings were from consanguineous matings and presented a wide range of phenotypic expressions. Minimal manifestations in 2 heterozygote carriers and the possibility of autosomal recessive inheritance are discussed.